Analisis Keberlanjutan Pembangunan Bendungan Way Sekampung, Lampung - Mirza Nirwansyah; Cecep Kusmana; Eriyatno Eriyatno; M.Yanuar J. Purwanto (JURNAL TEKNIK HIDRAULIK, 2018)
The availability of water resources provides many benefits for the welfare of all human being. The Decrease of the availability of water resources is caused by various reasons, including as environmental damage of catchment area, human activities, land conversion, and the issue of global warming. The problems caused an increase in floods and droughts. Dam development can reduce the risk of flood and drought through a reservoir operation by using less water during rainy season and using much water during dry season. The sustainability of water resources in Way Sekampung can be identified by three main indicators, which are ecology, economic, and sosio-cultural by using the MDS (Multi Dimensional Scaling) analysis, There are two item become the focus of this research i.e. sedimentation and water balance. These factors are considered as the most important factors in planning a dam. Operationally, this policy will be applied by supplying water based on demand, strengthening water resources institutions, improving infrastructure facilities and developing technology.